IMPLEMENTATION OF REGIONAL REGULATION NUMBER 3 OF 2016 CONCERNING WASTE MANAGEMENT IN BATANG REGENCY (CASE STUDY OF THE FINAL RANDU KUNING TEGALSARI REGENCY IN BATANG REGENCY) - Aditya Bryan Darmasaputra; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
ABSTRACT Waste in Tegalsari's Randu Kuning TPA is increasing every year. The more problems there are, the more garbage problems that continue to grow. The purpose of this research is to study and analyze the implementation of Regional Regulation No. 3 of 2016 in waste management in the Randu Kuning TPA, Tegalsari Batang Regency and the supporting and inhibiting factors that apply waste management in the Rals Kuning Tegal Tegalsari Batang Regency. The method used in this study uses a qualitative descriptive type. The analysis technique used is qualitative analysis. The results of the study stating the approval of Perda policy No. 3 of 2016 related to waste management in Tegalsari Randu Kuning TPA Batang Regency viewed from S. Grindle implementation theory, namely the contents of the policy of group interests, types of benefits, gender, choices to be sought, according to needs, Policy implementation, and resources used) and the policy environment (authority, interests and strategies of the actors involved, priority institutions and authorities, and the level of difficulty and response of implementers) of the phenomenon concluded as the implementation of Perda policy No. 3 Year 2016 concerning Waste Management in Tegalari Randu Kuning TPA Batang District cannot be approved with the aim and benefits of the local regulation not yet being approved by the community and implementing the policy. Constraints in the implementation of Perda policy No. 3 of 2016 concerning Waste Management in Tegalsari Randu Kuning TPA Batang Regency include socialization by related institutions or offices, improving facilities and infrastructure, staff supporting offer solutions in improving waste in TPA, hoping the community cares, officers TPA has difficulty finding garbage buyers, and the lack of strict punishment for violators of local regulations